Service Quality Factors of Healthcare System from COVID-19 Patients Perspectives - Hazmilah Hasan; Haeba Ali, Amena; Binti Akmal, Suriati (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper presents a study to investigate the service quality of healthcare system in UAE. The respondents are the users of the healthcare system. They were asked to grade the healthcare system through 25 items in five domains which are Reliability; Responsiveness; Assurance; Empathy and Tangibles. A total of 384 respondents participated in the questionnaire survey are COVID-19 patients discharged from UAE healthcare system. The analysis on the collected data found that three domains which are reliability, responsiveness and tangibles are having high level of satisfaction according to the respondent’s perspective in experiencing the healthcare during COVID-19 treatment. In term of ranking analysis, the responsiveness domain is ranked first with the highest score of 3.890, followed by reliability domain with mean score of 3.572, then tangibles domain with 3.533, empathy domain with 3.370 and finally assurance domain with 3.170. The findings from this study helps the healthcare practitioners in improving their service quality to the patients.